2004
DOI: 10.1099/mic.0.27254-0
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies in the essential Smp3 mannosyltransferase block glycosylphosphatidylinositol assembly and lead to defects in growth and cell wall biogenesis in Candida albicans

Abstract: Glycosylphosphatidylinositols (GPIs) are essential for viability in yeast and have key roles in cell wall construction. Assembly of Saccharomyces cerevisiae GPIs includes the addition of a fourth, side-branching mannose (Man) to the third Man of the core GPI glycan by the Smp3 mannosyltransferase. The SMP3 gene from the human pathogenic fungus Candida albicans has been cloned. CaSMP3 complements the inviable S. cerevisiae smp3 null mutant and, when expressed in an S. cerevisiae smp3/gpi13 double mutant, it per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…Many proteins in the cell wall and plasma membrane involved in fungal cell wall synthesis and assembly are GPI anchored, and GPI synthesis and/or anchoring is essential for cell viability in yeasts (27,29,43,46). Although there is a GPI core structure (ethanolamine-P-6Man␣1-2Man␣1-6Man␣1-4GlcNH 2 ␣1-6-D-myo-inositol-1-phosphate-lipid, where the lipid is either diacylglycerol, acylalkylglycerol, or ceramide) which is conserved in all eukaryotes (26), many subtle but significant differences that can occur as the result of additional species-specific modifications to the structure and assembly of GPI have been reported, leading to the notion that these could each be exploited as targets for new antifungal drugs (15,17). Some inhibitors of GPI biosynthesis have been reported (52,57), but most of these are designed based on acceptor analogs or protease inhibitors and do not possess drug-like properties.…”
Section: Discussionmentioning
confidence: 99%
“…Many proteins in the cell wall and plasma membrane involved in fungal cell wall synthesis and assembly are GPI anchored, and GPI synthesis and/or anchoring is essential for cell viability in yeasts (27,29,43,46). Although there is a GPI core structure (ethanolamine-P-6Man␣1-2Man␣1-6Man␣1-4GlcNH 2 ␣1-6-D-myo-inositol-1-phosphate-lipid, where the lipid is either diacylglycerol, acylalkylglycerol, or ceramide) which is conserved in all eukaryotes (26), many subtle but significant differences that can occur as the result of additional species-specific modifications to the structure and assembly of GPI have been reported, leading to the notion that these could each be exploited as targets for new antifungal drugs (15,17). Some inhibitors of GPI biosynthesis have been reported (52,57), but most of these are designed based on acceptor analogs or protease inhibitors and do not possess drug-like properties.…”
Section: Discussionmentioning
confidence: 99%
“…This posttranslational modification is required for the attachment of most of the MPs to the cell wall and, thus, also has a vital role in cell viability and wall integrity [146,147]. For example, repression of SMP3 expression, which encodes an essential mannosyltransferase for GPI elaboration, leads to cell-wall defects and loss of cell viability [148]. C. albicans mutants with defects in the bio synthesis of chitin [149,150], b1,3-and b1,6-glucans [151][152][153] have shown that these cell-wall components are important for cellwall integrity, cell viability and for virulence.…”
Section: N-and O-linked Mannans and The C Albicans-host Interactionmentioning
confidence: 99%
“…Contrary to PIG-O, Gpi13p requires a forth mannose (Man4) to be present on its substrate [68]. This by itself offers an explanation, why Smp3p, the mannosyltransferase adding the Man4, is essential in yeast and in C. albicans [68,69]. The human SMP3 homologue (hSmp3) is not expressed in many human cell lines, which however have no problem in GPI anchoring [70].…”
Section: Steps 8 and 9: Addition Of Man4 And Of Etn-p To Man3mentioning
confidence: 99%